On the asymptotic behavior of the solutions of nonstationary pseudolinear systems - Martynyuk, A.A.; Chernetskaya, L.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
We consider a class of pseudolinear systems of equations of perturbed motion. The sufficient conditions of boundedness and stability via integral inequalities are derived. As an example, we considered a linear system of equations with almost constant coefficients.